A Proteomic Platform Enables to Test for AML Normalization In Vitro - Meier-Menches, Samuel M.; Neuditschko, Benjamin; Janker, Lukas; Gerner, Marlene C.; Schmetterer, Klaus G.; Reichle, Albrecht; Gerner, Christopher (Frontiers in Chemistry, 2022)
Acute promyelocytic leukaemia (APL) can be cured by the co-administration of arsenic trioxide (ATO) and all-trans retinoic acid (ATRA). These small molecules relieve the differentiation blockade of the transformed promyelocytes and trigger their maturation into functional neutrophils, which are physiologically primed for apoptosis. This normalization therapy represents a compelling alternative to cytotoxic anticancer chemotherapy, but lacks an in vitro model system for testing the efficiency of novel combination treatments consisting of inducers of differentiation and metallopharmaceuticals. Here, using proteome profiling we present an experimental framework that enables characterising the differentiation– and metal-specific effects of the combination treatment in a panel of acute myeloid leukaemia (AML) cell lines (HL-60 and U937), including APL (NB4). Differentiation had a substantial impact on the proteome on the order of 10% of the identified proteins and featured classical markers and transcription factors of myeloid differentiation. Additionally, ATO provoked specific cytoprotective effects in the AML cell lines HL-60 and U937. In HL-60, these effects included an integrated stress response (ISR) in conjunction with redox defence, while proteasomal responses and a metabolic rewiring were observed in U937 cells. In contrast, the APL cell line NB4 did not display such adaptions indicating a lack of plasticity to cope with the metal-induced stress, which may explain the clinical success of this combination treatment. Based on the induction of these cytoprotective effects, we proposed a novel metal-based compound to be used for the combination treatment instead of ATO. The organoruthenium drug candidate plecstatin-1 was previously shown to induce reactive oxygen species and an ISR. Indeed, the plecstatin-1 combination was found to affect similar pathways compared to the ATO combination in HL-60 cells and did not lead to cytoprotective response signatures in NB4. Moreover, the monocytic cell line U937 showed a low plasticity to cope with the plecstatin-1 combination, which suggests that this combination might achieve therapeutic benefit beyond APL. We propose that the cytoprotective plasticity of cancer cells might serve as a general proxy to discover novel combination treatments in vitro.